The pteridophytes of São Tomé and Príncipe, Gulf of Guinea: who collected them and where? - Figueiredo, Estrela; Smith, Gideon F.; F. De Lima, Ricardo (Phytotaxa, 2024)
São Tomé and Príncipe, two islands in the Gulf of Guinea in the Atlantic Ocean off the central west coast of Africa, are well-known for their tropical, albeit substantially transformed, floras. Given the tropical climate prevalent in São Tomé and Príncipe, a large component of their floras is comprised of ferns and lycophytes—here collectively referred to as pteridophytes. We provide information on the collectors of pteridophytes in São Tomé and Príncipe during the colonial period (from the earliest times up to 1975). New information on these collectors and their collections are provided, and some of the doubts that existed about localities where pteridophytes were collected are solved.